Dampak Pembelajaran Diferensiasi dan PBL Terhadap Keterampilan Literasi Sains Peserta Didik di Sekolah Terpencil - Permatasari, Noni; Heriansyah, Heriansyah (Jurnal Didaktika Pendidikan Dasar, 2024)
The science literacy skills of students in remote schools lag significantly behind those in urban schools due to substantial differences in school conditions. This study aims to evaluate the impact of differentiated instruction combined with Problem-Based Learning (PBL) on the science literacy skills of students at SMP Negeri 43 Rejang Lebong. The research method used is descriptive quantitative. Data collection was carried out through observation and tests. The implementation of differentiated instruction with a learning style approach divides students into three categories (visual, audiotory, and kinesthetic) using the PBL method guided by worksheets (LKPD) tailored to the five aspects of science literacy skills on the topic of heat transfer. The results showed high student enthusiasm in learning activities across all three learning styles. However, two out of the five aspects of science literacy skills had average achievement levels below 50%. These aspects are understanding the components of research and their implications for scientific findings, and interpreting scientific data. The low achievement was observed across all three learning styles. Nonetheless, the other three aspects achieved between 50-76%, indicating that differentiated instruction combined with PBL has a positive impact on science literacy skills, particularly in remote schools.